Mutation of the signal peptide region of the bicistronic gene DSPP affects translocation to the endoplasmic reticulum and results in defective dentine biomineralization - Rajpar, M. Helen; Koch, Martin Jean; Davies, Robin M.; Mellody, Kieran T.; Kielty, Cay M.; Dixon, Michael J. (Human molecular genetics, 2002)
Dentine dysplasia type II is an autosomal dominant disorder in which mineralization of the dentine of the primary teeth is abnormal. On the basis of the phenotypic overlap between, and shared chromosomal location with, dentinogenesis imperfecta type II, a second disorder of dentine mineralization, it has been proposed that the two conditions are allelic. As recent studies have shown that dentinogenesis imperfecta type II results from mutation of the bicistronic dentine sialophosphoprotein gene (DSPP ), we have tested this hypothesis by sequencing DSPP in a family with a history of dentine dysplasia type II. Our results have shown that a missense change, which causes the substitution of a tyrosine for an aspartic acid in the hydrophobic signal peptide domain of the protein, underlies the phenotype in this family. Biochemical analysis has further demonstrated that this mutation causes a failure of translocation of the encoded proteins into the endoplasmic reticulum, and is therefore likely to lead to a loss of function of both dentine sialoprotein and dentine phosphoprotein.
Gesehen am 22.02.2021